Implementation and Effectiveness of Breastfeeding Policies in the Philippines Are Limited by Structural and Individual Barriers. (14th June 2022) - Castro, Mary Christine; Samaniego, Jyn Allec; Maramag, Cherry; Nguyen, Tuan; Cashin, Jennifer; Zambrano, Paul; Datu-Sanguyo, Janice; Weissman, Amy; Mathisen, Roger
Abstract: Objectives: To determine the content, implementation, and effectiveness of policies aimed at improving breastfeeding practices in the Philippines. Methods: This study used mixed methods, including a desk review of relevant policies and documents and in-depth interviews with 100 caregivers, workers, employers, health workers, and policymakers. Results: Although the Philippines has a strong regulatory framework to protect breastfeeding, the implementation and effectiveness of breastfeeding policies are limited by structural and individual barriers. Structural barriers include: a lack of consistent breastfeeding promotion, limited access to skilled counselling support from health system to community level, and limited breastfeeding support in workplaces for working mothers. Inappropriate marketing of commercial milk formula, including cross-promotion and engagement of industry representatives with health professionals, persists due to gaps in legal provisions and weak monitoring and enforcement of the Philippine Milk Code. Individual barriers include failure to address early breastfeeding problems, misconceptions that undermine breastfeeding, limited knowledge and skills of health workers and caregivers, and lack of support from family members. Conclusions: Breastfeeding promotion, protection, and support policies in the Philippines are consistent with global standards, but their effectiveness for improving breastfeeding practices can be improved by addressing persistent barriers at the structural and individual levels. Funding Sources: Bill & Melinda Gates Foundation (Grant Number OPP50838) and Irish Aid.